El proceso de globalización y sus impactos socio-políticos - Tomassini, Luciano (Estudios Internacionales, 1996)
This essay postulates that the globalization process, conceived as the worldwide diffusion of certain forms of knowledge, social production and life, capable of integrating the different spheres of all national societies into a global network, is the current dominant force in the world. This process preferably disseminates those guidelines that correspond to the current emerging culture. Thus, we are facing a cultural transformation that is equivalent to a change of era. All this calls into question the traditional ways of understanding society and doing politics, and poses important challenges to public policies through which the State tries to respond. The last two sections outline the transformation that the political process is undergoing under the impact of globalization, fundamentally based on observation and dialogue.